Pengaruh Persepsi Kemudahan Penggunaan, Brand Image, dan Gaya Hidup terhadap Keputusan Penggunaan Layanan Aplikasi Gopay - Andrew Mandala Setio; Benny Gunawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research examines and analyzes the influence of perceived ease of use, brand image and lifestyle simultaneously and partially on the decision to use Gopay application services. The research approach used in this research is quantitative research. The sample selection criteria in this study were those aged 17 years and over who had used Gopay in the Kebon Jeruk District area, West Jakarta. Questionnaires were collected from 100 respondents, the data was then processed using the multiple linear regression method. Based on the results of the analysis, it is known that the variables perceived ease of use, brand image and lifestyle simultaneously have a positive influence on the decision to use the Gopay application service. Partially, brand image and lifestyle variables have a positive influence on the decision to use Gopay application services. Meanwhile, partially the perceived ease of use variable has no influence on the decision to use the Gopay application service.